SIMULATION STUDY OF PET-COMPTON IMAGING SYSTEM USING MATERIAL GSO AND CZT AS DETECTOR MATERIAL OF ABSORBER RING - Suprobo Wangsaputra, Daniel
Positron Emission Tomography (PET) is known as a successful method for diagnosing cancer and molecular imaging. However, over time, imaging applications have become more widespread, such as in-vivo single cell level tracking, therefore some researchers recommended the PET application using direction information from Compton imaging because Compton imaging is the only method that capable of obtaining direction information from gamma rays who come without using a collimator. Based on this fact, QST and LMU work together to realize this PET-Compton by inserting a scatter ring into a PET ring, and this PET ring is used as an absorber ring. Based on papers published by QST and LMU, Gadolinium Orthosilicate material (Gd2SiO5 or GSO) is the best material for absober rings on PET-Compton. However, in papers published by NCBI, Cadmium Zinc Telluride (CdZnTe or CZT) is the best material used for PET. By using GAMOS, the PET-Compton system is simulated to find the value of sensitivity and energy resolution when using GSO and CZT material as a detector material from the absorber ring. By using variations in the diameter of the scatterer ring and the size of the crystal absorber in the form of the crystal thickness, the result obtained are figure IV.1, figure IV.2, figure IV.11, and figure IV.20. Based on this data, it can be concuded that GSO material with scatterer ring’s diameter 40 cm has the best sensitivity, 15.054%. The value of energy resolution is very depended by the size of the absorber crystal, therefore further research is needed by paying attention to cost effectiveness, thickness, and number of absorber layers.